Small Rewards Leverage Big Change: The Effect of M-Payment Rewards on Charitable Donations - Shi, Haijiao; Chen, Rong (Journal of Marketing Development and Competitiveness, 2019)
This study investigates how consumers perceive m-payment rewards and their disposition toward those rewards. Based on theories of mental accounting and across four studies, we find that consumers are more willing to donate when m-payment rewards are random (vs. regular), single (vs. cumulative) or immediate (vs. delayed), because consumers tend to perceive the rewards as more (vs. less) irrelevant to the previous purchase and thus are more (vs. less) willing to donate. We also reinforce the explanation of “rewards as windfall gains” by testing other subsequent choices in lotteries, hedonic consumption and indulgent consumption.